Perinatal Penicillin Exposure Affects Cortical Development and Sensory Processing - Perna, James; Lu, Ju; Mullen, Brian; Liu, Taohui; Tjia, Michelle; Weiser, Sydney; Ackman, James; Zuo, Yi (Frontiers in Molecular Neuroscience, 2021)
The prevalent pediatric use of antibiotics raises concerns about long-term risks for children’s health, but their effects on the central nervous system is not well understood. We studied the effects of perinatal penicillin exposure (PPE) on brain structure and function in mice with a therapeutically relevant regimen. We used a battery of behavioral tests to evaluate anxiety, working memory, and sensory processing at adolescence, and immunohistochemistry to quantify changes in parvalbumin-expressing inhibitory interneurons (PV+ INs), perineuronal nets (PNNs), as well as microglia density and morphology. In addition, we performed mesoscale Ca imaging to study neural activity and functional connectivity across cortical regions, and two-photon imaging to monitor dendritic spine and microglial dynamics. We found that PPE mice have altered sensory processing, including impaired texture discrimination and elevated prepulse inhibition. Such behavioral changes are associated with increased spontaneous neural activities in various cortical regions, and delayed maturation of PV+ INs in the somatosensory cortex. Furthermore, PPE mice show accelerated synaptic pruning during adolescent development and have significantly lower density of dendritic spines on the apical dendrites of layer 5 pyramidal neurons. Finally, while the density and baseline dynamics of cortical microglia are not altered, their ramifications and spatial coverages are increased in the PPE mouse brain, resulting in overlapping territories between neighboring microglia. Our study demonstrates that early-life exposure to antibiotics affects cortical development and neuronal circuit formation, leaving a lasting effect on brain functions.